Instructional design for ALAM Learning Management System (LMS): transforming storyboard pages into Adobe Flash interface/presentations / Shamsul Rizal Mohd Rosedi and Normaizura Mat Rom - Mohd Rosedi, Shamsul Rizal; Mat Rom, Normaizura (2018)
The electronic learning is gaining its significance either in complementing or replacing the traditional learning worldwide. This trend has also impacted the maritime education and training (MET) sector in Malaysia in which the eLearning poses challenges to the traditional delivery of the STCW (Standards of Training, Certification and Watchkeeping for Seafarers) courses. Trainers, as the prime movers of MET, have to explore and exploit the powerful features of eLearning in the delivery of their daily lessons. The Learning Management System (LMS) is the best platform to begin with as it provides the required facility to integrate innovative teaching approaches in classrooms. But the actual challenge is to develop and create interactive multimedia content for the LMS, as the content serves as stand-alone learning objects which can be accessed as anytime and anywhere by students. Hence, this paper sheds lights on the most practical part of the generic ADDIE model in Instructional Design, in which trainers cum developers move from pages of storyboard (planning stage) to the interface of the authoring software (development stage) when creating interactive multimedia content. Hopefully, this addresses the confusion and shortcomings in the critical development stage of any interactive multimedia content.